ANTIBIOTIC THERAPY OF NEGLECTED PERITONITISES - CLINICAL TRIAL - Gabriel STATESCU; Mihaela CARAUSU (Romanian Dental Association for Education, 2013)
the treatment with antibiotics represents one of the main components of the medical treatment of neglected peritonitises. Material and method: in principle, the antibiotics therapy must take place based on the bacteriological examination and with the results of the antibiogram in mind. However, in practice, because of the emergency situation and the polymorphism of bacteria we could also apply certain theoretical criteria in order to properly select the antibiotics treatment, but: the antibiotic must be active for the peritonitis germs; it must have a good penetration and it must concentrate in the peritoneal cavity; it must not any have toxic effects and must not be conducive to kidney failure. In our trial we have used a systematic antibiotics treatment in emergency situations, and we have often chosen combination of antibiotics following the analysis of the peritoneal pus and the antibiogram outcome. Results: The antibiotics used the most were Penicillin, Gentamicin, Metronidazole and Ampicillin. The combination of three antibiotics was used in 67.35% of all the cases when antibiotics were used. The antibiotics mostly used in an association of two were: Penicillin, Gentamicin, Ceftriaxone, Cefazolin. This association was used in 26.53% of the cases when antibiotics were used in the treatment. The most frequent antibiotics used in a combination of two for the treatment of acute appendicitis were: Ampicillin and Gentamicin, respectively Ampicillin and Metronidazole. The percentage of this association of the whole antibiotherapy for acute appendicitis represents 23.81%. In our trial we have compared the therapeutic proficiency of one antibiotic vs the combination of antibiotics in cases of neglected peritonitises. From our results we have found that there was an increased sensibility and a high rate of response (92%) in the patients treated with Imipenem and Netilmicin, in comparison with the rate of positive response of 83%, which we achieved when Imipenem was administrated in monotherapy. Conclusions: We have applied an algorithm of antibiotics therapy in a growing scale: Tienam (Imipenem) usually, in the 3 days until we have obtained the result of the antibiogram and we have become aware of the sensibility of the bacteria and had the possibility to choose a combination of antibiotics.